Polymorphism and Expression of HSD17Î²13 Gene and Its Association with Lamb Quality of Indonesian Sheep - Ratna Sholatia Harahap; Ronny Rachman Noor; Asep Gunawan (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2021)
HSD17Î²13 (17beta 13-Hydroxysteroid dehydrogenases) are important enzymes in steroid metabolism. This study investigated the polymorphisms and expression of the HSD17Î²13 gene in lamb quality traits in Indonesian sheep. A total of 200 of rams of seven breeds administered in the study were Javanese fat-tailed (JFT), Javanese thin-tailed (JTT), Garut sheep (GS), Jonggol sheep (JS), Garut composite sheep (GCS), Compass agrinac sheep (CAS), Barbados cross sheep (BCS) aged 10-12 months and weighed 20-30 kg. The Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) and MspI enzyme restriction were performed to identify the polymorphism of the HSD17Î²13 gene. The lamb quality traits were measured for physical quality, flavor, odor, and fatty acid composition. The results showed that the HSD17Î²13 gene was polymorphic and had three genotypes i.e., CC, CT, and TT. The highest genotype frequency was the CC when compared to the other genotypes. The allele frequency of HSD17Î²13 gene was not in Hardy Weinberg Equilibrium. The polymorphism of HSD17Î²13 gene was significantly (P<0.05) associated with the fatty acid composition and Saturated Fatty Acid (SFA), i.e., tridecanoic acid (C13:0), arachidic acid (C20:0), henecosanoic acid (C21:0), and tricosanoic acid (C23:0). The polymorphism was also significantly associated with the Monounsaturated Fatty Acid (MUFA) i.e. ginkgoleic acid (C17:1) and nervonoic acid (C24:1), and Polyunsaturated Fatty Acid (PUFA) i.e. eicosedienoic acid (C20:2). The level of expression of the HSD17Î²13 gene based on quantitative real time-PCR analysis results was not significantly different (P>0.05) among genotypes for lamb quality traits. It can be concluded that the polymorphism of HSD17Î²13 gene was associated with the fatty acid composition of lamb in Indonesian sheep.